2008
DOI: 10.1007/s10899-008-9105-9
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Types of Gambling Among Undocumented Mexican Immigrants in New York City

Abstract: There is a need to further explore both the prevalence and the severity of gambling amongst the growing population of undocumented Mexican immigrants in the U.S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…The study further noted that gambling disorder was comorbid with high rates of major depressive (14.1%), alcohol (22.9%), and posttraumatic stress (12.2%) disorders in that sample. More than half of the undocumented Mexican immigrants surveyed in a small study in New York City reported having gambled, and a majority of those gamblers played scratch and win tickets or the lottery (Momper et al 2009 ). Those who sent money home to their families or had lived in the United States more than 12 years and those who reported 1–5 days of poor mental health in the past 30 days were most likely to gamble.…”
Section: Introductionmentioning
confidence: 99%
“…The study further noted that gambling disorder was comorbid with high rates of major depressive (14.1%), alcohol (22.9%), and posttraumatic stress (12.2%) disorders in that sample. More than half of the undocumented Mexican immigrants surveyed in a small study in New York City reported having gambled, and a majority of those gamblers played scratch and win tickets or the lottery (Momper et al 2009 ). Those who sent money home to their families or had lived in the United States more than 12 years and those who reported 1–5 days of poor mental health in the past 30 days were most likely to gamble.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, studies in Western countries have suggested the importance of including ethnicity or race in accommodating cultural or religious differences in gambling activities (Scott and Garen, 1994; Stranahan and Borg, 1998a,b; Welte et al. , 2002, 2008; Momper et al. , 2009; among others).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, pathological gamblers in any racial and ethnic group in the United States (White, Black, Native American, Asian, or Hispanic) were more engaged in casino gambling than in non-casino gambling (Alegría, et al, 2009). In addition, undocumented Mexican immigrants in New York City who had lived in the United States for a longer period of time were more likely to have gambled at all than those who had more recently immigrated (Momper, Nandi, Ompad, Delva, & Galea, 2009). On the other hand, Wardman, el-Guebaly, and Hodgins (2001) found the Native American population was more likely to have problem or pathological gambling when compared to the general non-Native American population.…”
mentioning
confidence: 99%